Academic Commitment of Muslim Filipino Students in an Islamic Boarding School: A Phenomenological Study at Islamic Boarding School - Basir Jarah Anilon; Sjafri Sairin; Kamarodin Abas Abdulkarim; Mohammad Syifa Amin Widigdo; Fitriah M. Suud (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
This phenomenological study investigates the academic commitment of Muslim Filipino students attending Pondok Pesantren in Indonesia within the framework of transnational Islamic education. The research is grounded in Kobasa’s Academic Hardiness Theory and aims to understand how these students sustain long-term engagement in Islamic studies despite facing linguistic, cultural, and educational challenges. Using Colaizzi’s seven-step phenomenological analysis, data were gathered through semi-structured interviews, participant observation, and document analysis involving seven purposively selected participants. The findings reveal that academic commitment is nurtured through an interplay of personal, spiritual, and institutional factors. Structured daily routines, internalized religious motivation, and spiritual disciplines such as tahajjud, fasting, and Qur’an memorization serve as strong intrinsic drivers. At the same time, institutional vision, regulatory systems, peer collaboration, and family encouragement create a supportive ecosystem that reinforces persistence and resilience. Academic commitment among these students thus emerges not merely as persistence in study but as a spiritual journey integrating faith, self-discipline, and communal service. The study contributes to the growing discourse on Islamic educational resilience by demonstrating how faith-based pedagogy and pesantren culture cultivate enduring academic motivation across cultural boundaries. The implications emphasize the need for transnational Islamic education institutions to integrate contextualized, spiritually anchored learning frameworks that strengthen students’ moral identity, academic perseverance, and adaptive competence in multicultural environments.